2020
DOI: 10.1080/13854046.2020.1849803
|View full text |Cite
|
Sign up to set email alerts
|

Professional practices, beliefs, and incomes of U.S. neuropsychologists: The AACN, NAN, SCN 2020 practice and “salary survey”

Abstract: Objective: This portion of the 2020 survey updates practice information, beliefs, and income data of clinical neuropsychologists who practice within the United States. Methods: Doctoral-level neuropsychology practitioners were invited via numerous methods, with multiple reminders, to participate in a web-based survey from January 17 through April 2, 2020. The useable U.S. sample of 1677 doctoral-level practitioners was 6.2% larger than the comparable group in the prior 2015 practice survey. Results: Whereas wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
56
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 25 publications
8
56
1
Order By: Relevance
“…MMPI-2-RF/MMPI-3), are recommended for forensic examinations (Sherman et al, 2020). Such guidance is consistent with the vast majority of current practices of neuropsychologists when conducting clinical and forensic evaluations (Sweet et al, 2021b).…”
Section: Administration Of Svtsmentioning
confidence: 62%
See 4 more Smart Citations
“…MMPI-2-RF/MMPI-3), are recommended for forensic examinations (Sherman et al, 2020). Such guidance is consistent with the vast majority of current practices of neuropsychologists when conducting clinical and forensic evaluations (Sweet et al, 2021b).…”
Section: Administration Of Svtsmentioning
confidence: 62%
“…Specifically, with 1684 respondents answering relevant items pertaining to PVTs, Sweet, Benson, Nelson, and Moberg (2015) found that 91.2% of postdoctoral trainees, 88.5% of practitioners with no forensic experience, and 95.1% of practitioners with at least some forensic experience either "agree" or "strongly agree" that there is sufficient empirical research and knowledge to support the use of PVTs in practice. In a similarly-sized sample of 1699 respondents five years later (data collected in 2020), "agree" and "strongly agree" endorsements among these same three groups were 93%, 93.2%, and 95.3%, respectively (Sweet et al, 2021b). Interestingly, in the category of "strongly agree," non-forensic practitioners increased from 45.9% to 62.2% and forensic practitioners increased from 64.5% to 75% relative to 2015.…”
Section: New Consensus Considerationsmentioning
confidence: 91%
See 3 more Smart Citations